If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3p + 49 = 0 Reorder the terms: 49 + 3p = 0 Solving 49 + 3p = 0 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-49' to each side of the equation. 49 + -49 + 3p = 0 + -49 Combine like terms: 49 + -49 = 0 0 + 3p = 0 + -49 3p = 0 + -49 Combine like terms: 0 + -49 = -49 3p = -49 Divide each side by '3'. p = -16.33333333 Simplifying p = -16.33333333
| 3x+6=11y+4 | | 6x-8=5x-4 | | -42=-1.2x | | -7b=-91 | | 3y=-4+15 | | -6y-3y+6y+6x= | | ln(2x+5)=7 | | 1/2x2/5x3/4= | | 3/5(2/3) | | 6-3(x-2)+12=-2x+24-x | | 4-5c+2c-6c+2= | | 2x+48+4x-10+63+x=360 | | 22+8x=10-8 | | 6(20.57)-12=6y-18 | | 6x=144-x | | 4(2x+13)=30 | | 123-12=6y+18 | | 0.8n=8 | | 6+a=5 | | 2(n-67)=4 | | e/2=6 | | -1=c+9 | | X+(x-15)=95 | | -325=21x | | -3/2=-3/7u-4/3 | | 9x^1=27 | | 3x^4=21 | | 15c+2=25 | | (2+z)(4z+3)=0 | | .08f+.05s=1330 | | 14+23a=42+16a | | 1+6x-7x=4 |